Paralysed: A Systemic Functional Analysis of James Joyce’s “Eveline” - Monika Kavalir (ELOPE, 2016)
In homage to the work of Uroš Mozetič, the paper takes as its starting point previously developed suggestions about how the language of “Eveline” conveys a picture of the heroine as a passive, paralysed character. Using Hallidayan Systemic Functional Linguistics as a model of stylistic analysis, it investigates the contribution of both the ideational and the interpersonal metafunctions to the meaning of the text. The results extend and amend some ideas from the literature, such as the supposed prevalence of stative verbs, and suggest that while the short story as a whole predominantly uses material processes, their potential for change is mitigated by Joyce’s aspect, tense, and usuality choices. Eveline as the main character crucially has the role of a Senser, observing and internally reacting to the world around her, and even the processes in which she acts upon things and people are modalised and shown to be either hypothetical or instigated by others.